Changes in Fluorescent Intensity in Aniline with Benzoic Acid and Carbon Tetrachloride - Bakkialakshmi, S.; Shanthi, B.; Chandrakala, D.; Santhi, R. (Asian Journal of Chemistry, 2016)
The quenching of fluorescence of aniline by benzoic acid and carbon tetrachloride has been studied in benzene solvent at room temperature to understand the quenching mechanism. The Stern-Volmer plot has been found to be linear for both the quenchers. Regression coefficient (r), the Stern-Volmer constant (Ksv), Stoke’s shift, ionization potential, electron affinity and the solvent parameter have also been calculated. The results suggest that the quenching here is not static but dynamic in nature.